Efficacy and safety of fixed-dose losartan/hydrochlorothiazide/amlodipine combination versus losartan/hydrochlorothiazide combination in Japanese patients with essential hypertension. (April 2015) - Rakugi, Hiromi; Tsuchihashi, Takuya; Shimada, Kazuyuki; Numaguchi, Hirotaka; Nishida, Chisato; Yamaguchi, Hiroya; Shirakawa, Masayoshi; Azuma, Kyoichi; Fujita, Kenji P.
Abstract Japanese patients with uncontrolled essential hypertension received single-blind losartan 50 mg/hydrochlorothiazide 12.5 mg (L50/H12.5) for 8 weeks. Patients whose blood pressure (BP) remained uncontrolled were randomized double-blind to fixed-dose losartan 50 mg/hydrochlorothiazide 12.5 mg/amlodipine 5 mg (L50/H12.5/A5) or L50/H12.5 for 8 weeks followed by open-label L50/H12.5/A5 for 44 weeks. Adverse events were assessed. After 8 weeks, diastolic and systolic BP were reduced significantly more with L50/H12.5/A5 versus L50/H12.5 (both p < 0.001). Mean changes in diastolic and systolic BP were sustained for 44 weeks. L50/H12.5/A5 was well-tolerated and improved BP significantly versus L50/H12.5 in Japanese patients with uncontrolled essential hypertension.